Ca2+/calmodulin-dependent protein kinase II contributes to intracellular pH recovery from acidosis via Na+/H+ exchanger activation - Vila Petroff, Martin Gerarde (2010)
The Na+/H+ exchanger (NHE-1) plays a key role in pHi recovery from acidosis and is regulated by pHi and the ERK1/2-dependent phosphorylation pathway. Since acidosis increases the activity of Ca2+/calmodulin-dependent protein kinase II (CaMKII) in cardiac muscle, we examined whether CaMKII activates the exchanger by using pharmacological tools and highly specific genetic approaches. Adult rat cardiomyocytes, loaded with the pHi indicator SNARF-1/AM were subjected to different protocols of intracellular acidosis. The rate of pHi recovery from the acid load (dpHi/dt)—an index of NHE-1 activity in HEPES buffer or in NaHCO3 buffer in the presence of inhibition of anion transporters—was significantly decreased by the CaMKII inhibitors KN-93 or AIP. pHi recovery from acidosis was faster in CaMKII-overexpressing myocytes than in overexpressing β-galactosidase myocytes (dpHi/dt: 0.195 ± 0.04 vs. 0.045 ± 0.010 min− 1, respectively, n = 8) and slower in myocytes from transgenic mice with chronic cardiac CaMKII inhibition (AC3-I) than in controls (AC3-C). Inhibition of CaMKII and/or ERK1/2 indicated that stimulation of NHE-1 by CaMKII was independent of and additive to the ERK1/2 cascade. In vitro studies with fusion proteins containing wild-type or mutated (Ser/Ala) versions of the C-terminal domain of NHE-1 indicate that CaMKII phosphorylates NHE-1 at residues other than the canonical phosphorylation sites for the kinase (Ser648, Ser703, and Ser796). These results provide new mechanistic insights and unequivocally demonstrate a role of the already multifunctional CaMKII on the regulation of the NHE-1 activity. They also prove clinically important in multiple disorders which, like ischemia/reperfusion injury or hypertrophy, are associated with increased NHE-1 and CaMKII.